TV BRINGS BATTLE INTO THE HOME WITH THE VIETNAM WAR : An Augmented Reading Experience - Kenney, Karen Latchana; McCabe, Tracy; Schroeder, Alan (North Mankato, Minnesota : Compass Point Books, 2019)
"On-point historical photographs combined with strong narration bring the battles and controversies surrounding the Vietnam War to life. People saw the battles in real time, on the nightly news, changing forever how people viewed war. Readers will see it as well, both in the text and in the accompanying video clips via the free Capstone 4D app, creating an augmented reality experience that brings the printed page to life"--
t t
Includes index
"A 4D book"--Cover
Includes bibliographical pages : 63
Keywords: Vietnam War, 1961-1975 -- Press coverage -- Juvenile literature -- United States; Vietnam War, 1961-1975 -- Television and the war -- Juvenile literature -- United States; Press coverage